The influence of hip biomechanics on patellofemoral pain: Bibliographic Review (Research, Society and Development, 2020)
Patellofemoral pain can occur among young people even older sedentary ones, being more prevalent in young people. The characteristic symptoms are pain located in the anterior retropatellar and / or peripatellar region of the knee, presented during activities such as squatting, walking up / down trails, jumping and running. Muscle weakness in joints like the knee and the hip, has been shown to be symptomatic and developmental dysfunction modulators. The present literature aims to investigate the influence of hip biomechanics on symptoms of patellofemoral pain. This is a bibliographic review, including articles written in the English language, in the electronic databases LILACS, PubMed, SciELO and PEDro. A survey started in January 2020 and ended in February. As variables of interest, they were noted by one of the authors. In total, 15 articles were selected, excluding 6 items, including 9 in this review. The types of study were: Systematic Review (2), Meta-analysis (1), Cross-sectional descriptive study (1), Randomized Clinical Trial (4), Case-control study (1), with the total of final samples included in the sample 14 70 female and male individuals. Selected studies revealed that hip biomechanics directly influences the development of patellofemoral pain symptoms. The literature review shows that there is a direct relationship between femoral pain and hip biomechanics, which is excess adduction, internal rotation of the hip, muscle weakness of external rotators, hip extensors and abductors, enhancing the chance of showing the characteristic characters of the hip dysfunction.